Growth of Lactobacillus casei FNCC0900 in Media Based Umbi Porang Plant (Amorphophallus muelleri BI.) - Azhari, Fitri; Winarsa, Rudju; Siswanto, Siswanto; Muzakhar, Kahar; Utarti, Esti; Sutoyo, Sutoyo; Arimurti, Sattya (BERKALA SAINSTEK, 2021)
Porang tuber (Amorphophallus muellerii BI.) Is a type of tuber that has a high enough glucomannan content of 67%. Glucomannan is very difficult to digest by humans directly so it takes the role of probiotics. L. casei bacteria FNCC0900 as a probiotic agent capable of utilizing glucomannan as a carbon source for growth. The purpose of this study was to determine the growth pattern and changes in environmental factors, namely the pH value of the probiotic bacteria L. casei FNCC0900 growth medium. The parameters in this study consisted of the highest cell density, generation time and pH value changes in Glucose Yeast Peptone Liquid Media, Porang Boiled Water Media and Porang Flour Liquid Media using the drop plate method which had 4 repeated calculations. Porang Boiled Water Liquid Media has a faster log phase period with a higher cell density than Porang Flour Liquid Media, but the shortest generation time is found in Porang Flour Liquid Media with the highest number of generations. L. casei FNCC0900 bacteria are more able to reduce the pH of Glucose Yeast Peptone Liquid Media compared to porang tuber-based media, so in this case L. casei FNCC0900 can be stated to be able to grow on porang tuber-based media with growth patterns, generation time, cell density and pH value. which varies.